1994
DOI: 10.1016/0735-1097(94)90673-4
|View full text |Cite
|
Sign up to set email alerts
|

Acute hemodynamic effects of adjustable atrial septal defect closure in the lateral tunnel Fontan procedure

Abstract: These data demonstrate that a controlled right to left atrial shunt improves cardiac output and systemic oxygen delivery and facilitates the postoperative management of patients after the Fontan procedure. Atrial septal defect closure increases systemic saturation to normal values and prevents potential systemic embolization but significantly decreases oxygen delivery and might limit exercise tolerance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1995
1995
2009
2009

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The fenestration has been shown to reduce mortality, 46 decrease the incidence of early effusions after the procedure, and maintain left ventricular preload in times of hemodynamic stress. 13,14,68 Hemodynamic studies have shown that with temporary occlusion of such fenestrations or adjustable atrial septal defects (ASDs), 14,15,53,68,71,72 the cardiac output decreases, although the increase in oxygen saturation maintains oxygen delivery to the tissues. Rychik and colleagues 113 showed that late surgical fenestration for high cavopulmonary pressures after the Fontan may be beneficial.…”
Section: The Modified Fontan Operationmentioning
confidence: 99%
See 1 more Smart Citation
“…The fenestration has been shown to reduce mortality, 46 decrease the incidence of early effusions after the procedure, and maintain left ventricular preload in times of hemodynamic stress. 13,14,68 Hemodynamic studies have shown that with temporary occlusion of such fenestrations or adjustable atrial septal defects (ASDs), 14,15,53,68,71,72 the cardiac output decreases, although the increase in oxygen saturation maintains oxygen delivery to the tissues. Rychik and colleagues 113 showed that late surgical fenestration for high cavopulmonary pressures after the Fontan may be beneficial.…”
Section: The Modified Fontan Operationmentioning
confidence: 99%
“…Several techniques have been used for fenestration, including creation of an adjustable interatrial communication, 53,72 creation of a fixed fenestration by punching a hole in the Fontan baffle, 4 or exclusion of a single hepatic vein, allowing drainage into the pulmonary venous atrium. Progressive rightto-left shunting via intrahepatic collaterals resulted from hepatic vein exclusion, which has been abandoned as a means to provide a fenestration in the Fontan baffle.…”
Section: The Modified Fontan Operationmentioning
confidence: 99%
“…22 The fenestrations were subsequently closed using either an adjustable surgical technique, 23 or else a trans-catheter technique. 24 It became apparent that many patients were better with the fenestration open rather than closed, 25 so most groups now make no effort to close the fenestration. Some fenestrations will close spontaneously over time, indicating that whatever shortterm advantage is derived may not have a lasting effect.…”
Section: Fontan-surgical Techniquementioning
confidence: 99%
“…The major indication for baffle fenestration closure is to eliminate the risks of long-term right-to-left shunting. In addition to the use of surgically placed abdominal snares [1,3], a variety of transcatheter approaches to fenestration closure have been described [4 -7]. The newly developed Amplatzer septal occluder (AGA Medical, Golden Valley, MN) offers an alternative to other currently available devices.…”
Section: Introductionmentioning
confidence: 99%